2013
DOI: 10.1088/1748-9326/8/4/045031
|View full text |Cite
|
Sign up to set email alerts
|

Inundation, sedimentation, and subsidence creates goose habitat along the Arctic coast of Alaska

Abstract: The Arctic Coastal Plain of Alaska is characterized by thermokarst lakes and drained lake basins, and the rate of coastal erosion has increased during the last half-century. Portions of the coast are <1 m above sea level for kilometers inland, and are underlain by ice-rich permafrost. Increased storm surges or terrestrial subsidence would therefore expand the area subject to marine inundation. Since 1976, the distribution of molting Black Brant (Branta bernicla nigricans) on the Arctic Coastal Plain has shifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Based on the greenhouse gas fluxes measured in our study, we estimate that change in areal extent of vegetation communities that occurred following an increase in the number of geese broods from ~1000 to ~5000 in the 1990s [ Person et al ., ], may have increased the global warming potential of the net GHG emissions from this site by ~150%. Changes in goose population and in areas used by geese are occurring elsewhere in coastal Alaska as a result of climate and other environmental changes [ Flint et al ., , ; Tape et al ., ], and our results suggest that such changes could have substantial implications for GHG fluxes from these regions.…”
Section: Discussionmentioning
confidence: 65%
“…Based on the greenhouse gas fluxes measured in our study, we estimate that change in areal extent of vegetation communities that occurred following an increase in the number of geese broods from ~1000 to ~5000 in the 1990s [ Person et al ., ], may have increased the global warming potential of the net GHG emissions from this site by ~150%. Changes in goose population and in areas used by geese are occurring elsewhere in coastal Alaska as a result of climate and other environmental changes [ Flint et al ., , ; Tape et al ., ], and our results suggest that such changes could have substantial implications for GHG fluxes from these regions.…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, Arctic warming may have expanded the extent of C. subspathacea grazing habitat in recent decades. Tape et al () reported that in some coastal areas of the ACP, the availability of C. subspathacea meadows has increased because of the combined effects of permafrost deterioration and marine flooding. Conversion of freshwater sedges to halophytic graminoids has been associated with broad‐scale changes in the distribution of molting brant on the ACP (Flint et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, trough ponds are hydrologically and biogeochemically different from the polygon ponds that they often neighbor (Koch et al, 2014). Thus, a redistribution of water on Arctic landscapes may impact multiple processes including carbon cycling (Abnizova et al, 2012;Negandhi et al, 2014), aquatic ecosystem productivity (Breton et al, 2009;Crump et al, 2003;Hobbie, 1980), and wildlife habitat and food resources (Tape et al, 2013;Van Hemert et al, 2015).…”
Section: Introductionmentioning
confidence: 99%